Targeting the Microtubule EB1-CLASP2 Complex Modulates NaV1.5 at Intercalated Discs. Issue 3 (23rd July 2021) - Marchal, Gerard A.; Jouni, Mariam; Chiang, David Y.; Pérez-Hernández, Marta; Podliesna, Svitlana; Yu, Nuo; Casini, Simona; Potet, Franck; Veerman, Christiaan C.; Klerk, Mischa; Lodder, Elisabeth M.; Mengarelli, Isabella; et al.
Abstract : Rationale: Loss-of-function of the cardiac sodium channel NaV 1.5 causes conduction slowing and arrhythmias. NaV 1.5 is differentially distributed within subcellular domains of cardiomyocytes, with sodium current ( I Na ) being enriched at the intercalated discs (ID). Various pathophysiological conditions associated with lethal arrhythmias display ID-specific I Na reduction, but the mechanisms underlying microdomain-specific targeting of NaV 1.5 remain largely unknown. Objective: To investigate the role of the microtubule plus-end tracking proteins EB1 (end-binding protein 1) and CLASP2 (cytoplasmic linker associated protein 2) in mediating NaV 1.5 trafficking and subcellular distribution in cardiomyocytes. Methods and Results: EB1 overexpression in human-induced pluripotent stem cell-derived cardiomyocytes resulted in enhanced whole-cell I Na, increased action potential upstroke velocity ( V max ), and enhanced NaV 1.5 localization at the plasma membrane as detected by multicolor stochastic optical reconstruction microscopy. Fluorescence recovery after photobleaching experiments in HEK293A cells demonstrated that EB1 overexpression promoted NaV 1.5 forward trafficking. Knockout of MAPRE1 in human induced pluripotent stem cell-derived cardiomyocytes led to reduced whole-cell I Na, decreased V max, and action potential duration (APD) prolongation. Similarly, acute knockout of the MAPRE1 homolog in zebrafish ( mapre1b ) resulted in decreased ventricular conduction velocity and V max as well as increased APD. Stochastic optical reconstruction microscopy imaging and macropatch I Na measurements showed that subacute treatment (2–3 hours) with SB216763 (SB2), a GSK3β (glycogen synthase kinase 3β) inhibitor known to modulate CLASP2-EB1 interaction, reduced GSK3β localization and increased NaV 1.5 and I Na preferentially at the ID region of wild-type murine ventricular cardiomyocytes. By contrast, SB2 did not affect whole cell I Na or NaV 1.5 localization in cardiomyocytes from Clasp2 -deficient mice, uncovering the crucial role of CLASP2 in SB2-mediated modulation of NaV 1.5 at the ID. Conclusions: Our findings demonstrate the modulatory effect of the microtubule plus-end tracking protein EB1 on NaV 1.5 trafficking and function, and identify the EB1-CLASP2 complex as a target for preferential modulation of I Na within the ID region of cardiomyocytes. Graphic Abstract: A graphic abstract is available for this article. Abstract : Supplemental Digital Content is available in the text.